GE_GERICHTE C/1242/2018 vom 10. Januar 2020 - GE Cour de justice (2020)
FARDEAU DE LA PREUVE;PRINCIPE D'ALLÉGATION;OBLIGATION DE POSER DES QUESTIONS;DÉBUT | CPC.55.al1; CPC.56; CPC.150; CPC.247.al1; CO.102.al1; CO.104